Strategic importance of corporate accounting policies - V. M. Rumyantseva (Учёт. Анализ. Аудит, 2022)
The paper describes issues of improving the accounting policy as a fundamental methodological tool for organizing and implementing the accounting process and the reporting of an economic entity formed on its basis, which is the primary source of information about its financial activities. Reporting and accounting policies should be in a stage of constant development and evolution in order to meet adequate business development trends and the needs of stakeholders. In an environment where corporations are the basic form of business organization, corporate reporting, showing the process of creating value over time, results from the development of the existing merged reporting model, and corporate accounting policy is a corporate governance tool. At the same time, levelbased risk-based approach to its implementation can be considered as a tool for implementing a corporate strategy. The purpose of the research is to identify trends in improving corporate accounting policies, and the task is to update its strategic significance. In the course of the work, the author substantiates the expansion of the boundaries and functions of accounting policy in the corporate space as endowing it with the functions of a corporate governance instrument and the implementation of corporate strategy. The results of the study can be used for the purposes of corporate governance and optimization of the coordinated activities of participants in corporate relations. This caused to the process of implementing a single strategy by revealing the management functions of accounting systems and updating their predictive risk-based value.